Strengthening Rule of Law in the Legislative Process in Indonesia - Rahmad Satria; Purwanto Purwanto; Agustinus Astono (JURNAL AKTA, 2026)
The principle of rule of law is the main foundation of the state of law which requires that the process of forming laws be carried out in a constitutional, transparent, accountable, and participatory manner. However, in the practice of legislation in Indonesia, various laws often receive criticism due to weak procedural compliance, lack of meaningful public participation, and increasing formal testing in the Constitutional Court. This condition shows that there is a gap between the legal norms of the formation of laws and regulations and the actual practice of legislation. This study aims to analyze and evaluate the strengthening of the principle of rule of law in the legislative process in Indonesia by examining the relationship between the normative framework of law-making and the institutional practice of law-making. This study uses the doctrinal-socio-legal research method with a qualitative approach, which combines normative analysis of laws and regulations and the principles of the state of law with empirical analysis based on official documents of the legislation process, including academic manuscripts, minutes of DPR meetings, list of problem inventories, and statements of the DPR and the Government in the Constitutional Court's decision. The data is analyzed qualitatively through legal reasoning and content analysis. The results of the study show that although the regulatory framework for the formation of laws has accommodated the principle of rule of law, its implementation is still formalistic and does not fully guarantee meaningful public participation. This study concludes that strengthening the rule of law in the legislative process requires procedural reform and strengthening accountability mechanisms to ensure the quality of constitutional and democratic legislation.